Caio Fernando Abreu? Li no Facebook - Nascimento, Mariane Tarragô (2016)
The present work intends to analyze two pages in the Facebook dedicated to the writter Caio Fernando Abreu, observing in what way his literature appears on the web. It’s, still, important for us, inquire the way this tool became part of our lives and how, undeniably, it changed the way of consuming literature, specially with regards about the writter Caio Fernando Abreu. It’s exactly for this feature that the study of Facebook’s approach with literature seams promising. Discussing about his uses in the comporaneity and the way it changed through Facebook is our focus of concerns. Once we share an art stretch, we ran away from the conventional reading’s rituals (individual’s, alone’s), because, through the social net, it became shared with many people. So, considering as the literature interacts with the social through the technology and how Caio Fernando Abreu’s work can be shared are rich questions to our research.